Call my Rep! How Unions Overcame the Free-Rider Problem - Richard Murphy (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper proposes an explanation of why union membership has been increasing in some occupations, despite the opportunity to freeride on traditional union benefits. I model membership as legal insurance whose demand increases with the perceived risk of allegations. Using media reports on allegations against teachers as shocks to perceived risk, I find for every five reports occurring in a region, teachers are 2.5 percentage points more likely to be members in the subsequent year. These effects are larger when teachers share characteristics with the news story and explain 45 percent of the growth in teacher union membership since 1992.
Keywords: J51; J45; J32; 330; unions; teachers; media; insurance